Factors influencing intention to use diminishing partnership home financing - Abdul Razak, Dzuljastri; Md Taib, Fauziah; Ramayah, T. (Emerald Group Publishing, 2008)
Abstract Purpose – The purpose of this study is to examine the acceptance level of a new Islamic home financing concept, diminishing partnership (DP), by consumers in Malaysia using the theory of reasoned action as the guiding principle. Design/methodology/approach – Cross sectional data were collected through a survey and analysed by means of factor analysis, correlation and regression analysis. Findings – Positive attitude or degree of favorableness towards the DP concept and religious and social influence are jointly responsible in determining the intention to engage in DP though the former commands greater influence. Research limitations/implications – The use of convenience sampling and postgraduate students may not sufficiently capture the variations that could potentially exist in the market. Practical implications – Introducing a leading Islamic finance product requires more than just a mere Shariah Board approval as customers are far more critical than has often been assumed. Demand for the home diminishing product has clearly been substantiated. It is a challenge for bankers to devise products that use the spirit of the concept very closely without compromising its salient features. Marketing strategies to consumers with different religious backgrounds have also been identified. Originality/value – This study examines customers’ acceptance level of a new Islamic home financing concept among multi ethnic/religion consumers with growing interest and consciousness about Islamic financial products.